Immunomodulator Testing on Ethanol Extract of Gynura procumbens Leaves to Mus musculus Adaptive Immune System: in Vitro Study - Dwijayanti, Dinia Rizqi; Rifa'i, Muhaimin (Graduate School, Universitas Brawijaya, 2014)
Immunomodulator is a substance that has an ability to modulate the activity and function of immune system. Gynura procumbens supposed to has benefit as an immunomodulator because of it afficacy to cure many diseases. The aim of this study is to determine the effect and dose variations of G. procumbens extract on biological aspect of CD4+CD62L-, CD4+CD62L+, CD8+CD62L- and CD8+CD62L+ T cells. G. procumbens extract concentrations that used in this experiment were 0 µg /ml, 0.1 µg/ml, 1 µg/ml, and 10 µg/ml. Spleen cells were cultured for 4 days in 5% CO2 incubator at a temperature of 37°C. Cultured cells were harvested and analyzed by flowcytometry to asses cell surface molecule expression. The resulting data were tabulated and analyzed using ANOVA analysis with a significance of 0.05% on SPSS version 16. Results showed that the extract of G. procumbens can increase the proliferation of CD4+CD62L-, CD4+CD62L+, CD8+CD62L- and CD8+CD62L+ T cells compared to the control. Dose of 1 µg/ml showed the highest effect to promote cell activation compared with the dose of 0.1 µg/ml and 10 µg/ml. Dose of 10 µg/ml could suppress CD4+CD62L-, CD4+CD62L+, CD8+CD62L- and CD8+CD62L+ T cells development. This study suggests that the ethanol extract of G. procumbens has benefit as an immunomodulator and involved in the immune system. Keywords: Gynura procumbens, immunity, immunomodulator, in vitro, lymphocytes.